Poly-victimization and post-traumatic stress symptoms in care experienced youth: the mediating role of mentalizing - Olivia Lucia Marie Emmerich; Nina Heinrichs; Birgit Wagner; Betteke Maria van Noort (European Journal of Psychotraumatology)
Background: Youth with care experience have often been affected by repeated victimization and exhibit high rates of post-traumatic stress symptoms (PTSS). Several studies underline the buffering role of mentalizing against the harmful effects of childhood adversity.Objective: This study aims to assess whether lower mentalizing mediates the relationship between poly-victimization and PTSS in youth with care experience.Method: 103 participants (75% female) with care experience, who were not currently or had not previously lived with their biological parents, aged 14–21 years (M = 17.81, SD = 2.24), completed the Juvenile Victimization Questionnaire (JVQ-R2), the Reflective Functioning Questionnaire (RFQ), and the Child Revised Impact of Events Scale (CRIES-8). Using structural equation modelling mentalizing was tested as a mediator on the relationship of poly-victimization and PTSS.Results: Juvenile victimization experiences significantly predicted PTSS (β = .37, p = .008) and lower mentalizing (β = .31, p = .006), which in turn predicted PTSS (β = .56, p < .001). The relationship between poly-victimization and PTSS was partially mediated by mentalizing (β = .17, 95%-CI [.06, .38], p = .002).Conclusions: Results suggest that poly-victimization is associated with lower mentalizing and higher PTSS. Lower mentalizing, in turn, is linked to higher PTSS. Findings highlight the potential of interventions fostering mentalizing in care-experienced youth.